Bifunctional Therapeutic Peptides for Targeting Malignant B Cells and Hepatocytes: Proof of Concept in Chronic Lymphocytic Leukemia. Issue 12 (12th October 2020) - Simon‐Gracia, Lorena; Savier, Eric; Parizot, Christophe; Brossas, Jean Yves; Loisel, Severine; Teesalu, Tambet; Conti, Filomena; Charlotte, Frederic; Scatton, Olivier; Aoudjehane, Lynda; Rebollo, Angelita
Abstract: Protein–protein interactions are well recognized as therapeutic targets and therefore interfering peptides (IP) that block these interactions are receiving increasing attention. Four different tumor‐penetrating peptides (TPPs) (iRGD, RPARPAR, Linear TT1 (LinTT1), and cyclic TT1 (TT1)) are associated to an IP that blocks the interaction between the protein phosphatase PP2A and its binding protein SET, generating new bifunctional peptides able to intracellularly target the PP2A/SET interaction in malignant B cells and tumoral hepatocytes. The TPPs are able to penetrate into B cells of patients suffering chronic lymphocytic leukemia (CLL) and into tumoral hepatocytes but not into B cells from healthy donors and healthy hepatocytes. The association of cargo does not affect the penetration of the TPPs in CLL B cells. All the bifunctional peptides induce apoptosis in human CLL B cells and tumoral hepatocytes, and stability tests reveal that iRGD‐IP, RPARPAR‐IP, and TT1‐IP are stable after 24 h incubation in human serum. The iRGD associated with the IP significantly increases the survival of mice bearing xenograft models of CLL without any symptom of toxicity, suggesting that the bifunctional peptides may have a therapeutic application for selective tumoral targeting of PP2A/SET interaction, which is deregulated in several cancers, including CLL. Abstract : Interfering peptides that block protein/protein interactions are considered as promising therapeutic targets. The association of a tumor‐penetrating peptide to the interfering peptide gives a new capability and specificity to these bi‐functional peptides allowing tumoral targeting. Progress on peptide administration, stability, biodelivery and safety also encourages interest in peptide drug development.